Darbas, nesustodavęs net Viešpaties dieną. Zigmanto I darbadieniai Lietuvos Didžiosios Kunigaikštystės teisme 1506–1544 metais - Saviščevas, Eugenijus (Vilnius University Open Series, 2024)
The selection of the judicial acts of Sigismund I preserved in the Lithuanian Metrica showed that when conducting investigations of the ruler’s employment at court, we must take into account the uneven nature of the documents. We can distinguish 4 types of judicial acts: judgments or sentences, ordinances (orders), pre-trial or post-trial documents and minutes (drafts). 3081 acts were selected for this study, only about half of which are recorded in court record books, and the rest in books of inscriptions. The most numerous types of acts are ordinances, which make up more than half of all the judicial acts (1629) of Sigismund I. Due to the breadth of the ruler’s judicial functions and their interweaving with other types of activities, the methodology of selecting and sorting judicial documents is not protected from the subjective decisions of the researcher. Therefore, the quantitative expressions achieved by the research must be understood as relative. However, they also allow us to see the dynamics of the ruler’s judicial activity: in the first half of the reign of Sigismund I (1506–1521), the ruler’s judicial activity was not active, but from 1522 it began to grow noticeably, reaching its apogee in 1533. Later, the activity steadily decreased. Judging by the ruler of Lithuania (probably not only Sigismund I) took place in two different phases: during the ruler’s residence in the Grand Duchy of Lithuania, when his judicial activity became more active, and in the Crown, when his activity weakened. Almost always, the most active time of the first phase coincided with the Seim of the Grand Duchy of Lithuania. However, during the penultimate visit, Sigismund I handled most of the cases outside the Seim time. The dynamics of judicial documents in general and judgments in particular (i.e. the resolution of cases) show that starting from 1523 he was increasingly active as a judge in the cases of residents of the Grand Duchy of Lithuania while he was in Poland. Despite the resulting protests and in 1542 the ruler’s promise not to judge “Lithuanian cases” in Poland, this practice continued even later, but it was not significant. The accounting of Sigismund I’s working days per year showed the chaotic nature of the activity of the ruler-judge. Quantitative analysis of judicial acts preserved in Lithuanian Metrics does not allow us to claim that the ruler’s agenda was overloaded with the obligation to judge. However, qualitative factors (judging on Sundays, during Holy Week and during Christmas) testify to the constant pressure exerted by the litigating authorities on the person of the ruler. This was the essence of the ruler’s burden of judging.